(untitled) (Indian Journal of Child Health, 2024)
Background: In 1993, Richardson et al. introduced the score for neonatal acute physiology (SNAP), a 34-parameter system predicting mortality and morbidity in neonates. To enhance simplicity, it was later refined to nine parameters and renamed SNAP-II. Additionally, a perinatal extension known as SNAP Perinatal Extension, Version II (SNAPPE-II) was developed for broader applicability. Objectives: To determine the validity of SNAPPE-II in predicting the outcome in terms of mortality in premature babies of gestational age between 32 and 36 weeks in a tertiary care neonatal intensive care unit (NICU) of Cheluvamba Hospital, Mysore, Karnataka. Materials and Methods: The diagnostic study was conducted in the NICU of a tertiary care center in Mysore, India. The sample size of 138 subjects was calculated using a formula, and simple random sampling was used. The study included newborns with gestational ages between 32 and 36 weeks, and data was collected within 48 h of birth as per the proforma. The study assessed the correlation between the SNAPPE II score and mortality rate in babies admitted to the NICU. Data were analyzed using various statistical methods. Results: This study finds that the SNAPPE-II score has a moderate ability to distinguish between those newborns who will end up with mortality and those who will survive, as indicated by an area under ROC curve of 0.724, and has moderate diagnostic accuracy as indicated by a Youden index of 0.3974. The associated criterion for the SNAPPE-II score is >57, indicating newborns are more likely to have mortality. Conclusion: The SNAPPE-II score can be used to predict neonatal mortality rates in moderate-to-late preterm babies of gestational age between 32 and 36 weeks.